Karakteristik Dari Penderita Fraktur Femur di RSUP Haji Adam Malik Medan Periode Januari 2009 – Desember 2010 - Andriandi dr; Chairiandi Siregar (Fakultas Kedokteran USU, 2014)
Objectives : To know the charachteristic of femoral fracture patients in RSUP Haji Adam Malik Medan period of Januari 2009- Desember 2010.Background : Femoral fracture has a high incidence among other kinds of fracture that can caused the serious physical suffering, mentally affected, and loss time of daily working of patients. Thus femoral fracture have low mortality rate but with high morbidity rate. The method of prevention can be done by identifying the related variables through the epidemiology studies comprehensively.Method : Collecting the secunder data that recorded on medical record of patients that diagnosed femoral fracture in RSUP. Haji Adam Malik Medan (RSUP HAM) period of Januari 2009 – Desember 2010.Results : Found that femoral fracture in RSUP HAM most cases is male with age 21-30 years old that cause 93.92 % by traffic accident. Most region of fracture is mid-diaphysis about 54.7%. Also found about 179 samples (72.46%) from outside Medan with most of education level is elementary school about 178 subjects (72.06 %). And they were brought to the RSUP HAM below than 72 hours is about 163 subjects (66.0%). For the subjects with age 0-50 years, most often region of femoral fracture is mid diaphysis, meanwhile for age above 50 years old is neck femur. For the fracture classification, found that closed fracture is more often than open fracture femoral fracture.Conclusion : Most of femoral fracture patient in RSUP HAM is male that classified as productive age caused by road traffic accident. And most of them is in mid diaphysis region of femoral. The preventive method by focusing to decrease incidence of road traffic accident is the main priority followed by improving the tools and skills for treating the femoral fracture cases. Keywords : fracture, femoral, trauma